Reinventing postgraduate training in the plant sciences: T‐training defined through modularity, customization, and distributed mentorship. (20th November 2018) - Henkhaus, Natalie A.; Taylor, Crispin B.; Greenlee, Vanessa R.; Sickler, Delanie B.; Stern, David B.
Abstract: The Plant Science Research Network (PSRN) comprises scientific societies and organizations with a mission to build and communicate a consensus vision of the future of plant science research, education, and training. This report enumerates a set of far‐reaching recommendations for postgraduate training that emerged from workshops held in October 2016 and September 2017. These recommendations broaden and deepen the T‐training concept presented in the Decadal Vision for Plant Science, which emphasizes experiential learning beyond the traditional disciplinary focus. Both workshops used the scenarios developed in Imagining Science in 2035 as a mechanism to encourage out‐of‐the‐box thinking, an approach that led to the innovative recommendations and solutions described here. At the heart of our recommendations is the empowerment of trainees, who should be enabled to customize and take ownership of their training experiences. This fundamental concept is embodied in five principles: (a) Trainees should be provided guidance and resources needed to define and pursue career objectives within and beyond academia, conferring to them greater independence and responsibility in shaping their own future. (b) Learning should be flexible, adaptable, and distributed. Training should combine traditional and modular coursework to encompass both technical and professional skills. Guidance from diverse mentoring teams will support and tailor training toward diverse, personalized career paths. (c) Scientific research experiences should be broad and question‐driven, whether motivated by basic discovery or seeking solutions to societal challenges. Trainees should continue to gain mastery of one or a few core scientific disciplines and their key tools and approaches. (d) Trainees should be skilled in science communication and incentivized to engage with and learn from the broader public community, helping to maintain an active dialogue among public, private, and academic sectors. (e) Training programs should foster and facilitate the inclusion of individuals with a diverse range of life experiences and should prioritize trainee well‐being. The report recommendations call for a profound cultural shift, one that embraces and extends educational delivery trends toward self‐learning and distance learning, considers trainee well‐being as an essential requirement for success, and acknowledges the importance of effective two‐way communication with the public. This shift is intended to broaden participation in the plant science workforce, both in terms of diversity and numbers, while maintaining excellence in core scientific training. Cultural change takes time, but among academic institutions the need for significant change and innovation in postgraduate training is increasingly pressing. As such, the immediate intent is for these recommendations to catalyze pilot programs and also build on emergent prototypes that exist globally while creating momentum for larger scale changes over longer time periods.